ANALISIS DAN PERANCANGAN E-GOVERMENT DALAM TRANSPARANSI SISTEM PEMERINTAHAN DESA: (Studi Kasus : Desa Tenjo Layar dan Desa Tanjung Sari Majalengka) - Abdurahman, Dede; Ferga Prasetyo, Tri (Jurnal Mnemonic, 2018)
Fast, accurate and accurate information needs to be one of the basic development of information and communication technology. The type of service and support in the field of information and communication technology (ICT) on governance is a strategic part in ensuring the improvement of service quality and support in applying e-Government to Village Governance.Village Governance and clean, transparent public services are challenges that the village government must answer in performing its functions as a public servant. With infrastructure facilities in the field of ICT already available in the village and administrative issues that need to get serious attention, thereby encouraging Researchers to utilize existing ICT infrastructure by analyzing and designing e-government applications that suit the needs of the village and in accordance with the Village Law article 4 letter f which reads to improve public services for the villagers to accelerate the realization of general welfare, and article 7 paragraph 3 letter c which reads accelerate the improvement of public service quality.